Human endothelial colony forming cells from adult peripheral blood have enhanced sprouting angiogenic potential through up-regulating VEGFR2 signaling. (15th October 2015) - Joo, Hyung Joon; Song, Sukhyun; Seo, Ha-Rim; Shin, Jennifer H.; Choi, Seung-Cheol; Park, Jae Hyoung; Yu, Cheol Woong; Hong, Soon Jun; Lim, Do-Sun
Abstract: Background: Endothelial colony forming cells (ECFCs), a subtype of endothelial progenitor cells, have been studied as a promising cellular source for therapeutic angiogenesis. Although ECFCs are very similar to mature endothelial cells, details regarding the role of ECFCs during angiogenesis are not known. We compared the cellular and angiogenic properties of ECFCs and mature endothelial cells (HUVECs). Methods: HUVECs were used as control. Quantitative RT-PCR, western blotting, immunofluorescence staining, flow cytometric analyses and angiogenic cytokine array were performed. 3D-microfluidic angiogenesis assay system was adopted for in vitro angiogenic potential. In vivo angiogenic potential was assessed by Matrigel plug assay. Results: ECFCs had higher expression of activated endothelial tip cell markers (Dll4, CXCR4, CD34, and VCAM1) and arterial genes (DLL4 and CX40), but lower expression of venous and lymphatic genes (COUP-TFII and PROX1). In 3D-microfluidic angiogenesis assay system, ECFCs induced robust sprouting vascular structures. Co-cultivation of both ECFCs and HUVECs gave rise to lumen-formed hybrid vascular structures, with the resulting ECFCs predominantly localized to the tip portion. This finding suggests that the ECFC has a role as a sprouting endothelial tip cell. Interestingly, VEGF-A phosphorylated VEGFR2 and its downstream signaling molecules more strongly in ECFCs than in HUVECs. Even small amount of VEGF-A successfully induced the sprouting angiogenesis of ECFCs. Finally, co-administration of ECFCs and human dermal fibroblasts successfully induced lumen-formed maturated neovessels in vivo. Conclusion: ECFCs derived from adult peripheral blood had enhanced sprouting angiogenic potential in vitro and in vivo through up-regulation of the VEGFR2 signaling pathway. Graphical abstract: Highlights: 3D-microfluidic system mimics in vivo angiogenesis under defined conditions. ECFC has stronger angiogenic potential compared to HUVEC in 3D-microfluidic system. ECFC is more sensitive to VEGF-A stimulation compared to HUVEC. Implantation of ECFC and dermal fibroblasts induce robust in vivo neovascularization.